2013
DOI: 10.1371/journal.pone.0084023
|View full text |Cite|
|
Sign up to set email alerts
|

Biosynthesis of Firefly Luciferin in Adult Lantern: Decarboxylation of ʟ-Cysteine is a Key Step for Benzothiazole Ring Formation in Firefly Luciferin Synthesis

Abstract: BackgroundBioluminescence in fireflies and click beetles is produced by a luciferase-luciferin reaction. The luminescence property and protein structure of firefly luciferase have been investigated, and its cDNA has been used for various assay systems. The chemical structure of firefly luciferin was identified as the ᴅ-form in 1963 and studies on the biosynthesis of firefly luciferin began early in the 1970’s. Incorporation experiments using 14C-labeled compounds were performed, and cysteine and benzoquinone/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…In an amazing feat of in vivo chemistry that remains somewhat mysterious, the firefly synthesizes D-luciferin in a multi-step process from L-cysteine and benzoquinone [47]. In the laboratory, D-luciferin and aminoluciferin analogs are typically synthesized by the condensation of an electron-deficient nitrile with D-cysteine (Figure 3).…”
Section: In Vivo Synthesis Of Luciferinsmentioning
confidence: 99%
“…In an amazing feat of in vivo chemistry that remains somewhat mysterious, the firefly synthesizes D-luciferin in a multi-step process from L-cysteine and benzoquinone [47]. In the laboratory, D-luciferin and aminoluciferin analogs are typically synthesized by the condensation of an electron-deficient nitrile with D-cysteine (Figure 3).…”
Section: In Vivo Synthesis Of Luciferinsmentioning
confidence: 99%
“…darwiniensis soldiers, the identified chemical compounds are thought to be mixed in the labial glands (Sillam‐Dusses et al ., ) with p ‐benzoquinone being the dominant component found in secreted fluids (Moore, ) (Table ). The process of quinone production had been hypothesized in Eleodes longicollis and Tribolium castaneum (Happ, ), and also as a part of luciferin biosynthesis in the firefly Luciola lateralis (Oba et al ., ) but the pathways responsible for the production of these chemicals has remained largely unclear. In our study, we identified glucosylceramidase, oxidoreductases (in particular, glucose dehydrogenase [FAD‐quinone]) and laccase 2, which are likely to be involved in the of benzoquinone biosynthesis in soldier secretions.…”
Section: Discussionmentioning
confidence: 97%
“…The synthesis of d ‐luciferin in the laboratory typically employs condensation of 2‐cyano‐6‐hydroxybenzothiazole with d ‐cysteine as the final step . Although early work suggested this reaction can occur upon co‐injection of 2‐cyano‐6‐hydroxybenzothiazole and d ‐cysteine into firefly lantern organs , this is not likely the method that fireflies use to make their luciferin . First, amino acids are made in the l ‐form, and there is no evidence of excess d ‐cysteine in firefly lanterns.…”
Section: Biosynthesis Of D‐luciferinmentioning
confidence: 99%